Energetically efficient electrochemically tunable affinity separation using multicomponent polymeric nanostructures for water treatment. Issue 10 (25th July 2018) - Mao, Xianwen; Tian, Wenda; Ren, Yinying; Chen, Dexin; Curtis, Sarah E.; Buss, Marjorie T.; Rutledge, Gregory C.; Hatton, T. Alan
Abstract : We describe a water treatment strategy, electrochemically tunable affinity separation (ETAS), which, unlike other previously developed electrochemical processes, targets uncharged organic pollutants in water. Abstract : We describe a water treatment strategy, electrochemically tunable affinity separation (ETAS), which, unlike other previously developed electrochemical processes, targets uncharged organic pollutants in water. Key to achieving ETAS resides in the development of multicomponent polymeric nanostructures that simultaneously exhibit the following characteristics: an oxidation-state dependent affinity towards neutral organics, high porosity for sufficient adsorption capacity, and high conductivity to permit electrical manipulation. A prototype ETAS adsorbent composed of nanostructured binary polymeric surfaces that can undergo an electrically-induced hydrophilic–hydrophobic transition can provide programmable control of capture and release of neutral organics in a cyclic fashion. A quantitative energetic analysis of ETAS offers insights into the tradeoff between energy cost and separation extent through manipulation of electrical swing conditions. We also introduce a generalizable materials design approach to improve the separation degree and energetic efficiency simultaneously, and identify the critical factors responsible for such enhancement via redox electrode simulations and theoretical calculations of electron transfer kinetics. The effect of operation mode and multistage configuration on ETAS performance is examined, highlighting the practicality of ETAS and providing useful guidelines for its operation at large scale. The ETAS approach is energetically efficient, environmentally friendly, broadly applicable to a wide range of organic contaminants of various molecular structures, hydrophobicity and functionality, and opens up new avenues for addressing the urgent, global challenge of water purification and wastewater management.